(untitled) (Revista Internacional de Folkcomunicação, 2024)
This article examines how ex-votive narratives intertwined with biomedicine reflect popular health practices through folk communication. We analyzed ex-votos in the Sala de Milagres at the Basílica do Senhor do Bomfim and testimonials of graces from the Irmã Dulce Memorial, noting how faith blends with limited access to conventional medical treatments. Employing qualitative methods, such as document analysis and content analysis, the study highlights how ex-votos manifest individual and collective relationships with biomedicine. These objects and popular narratives serve as communicative mediums that incorporate ordinary knowledge and resist dominant epistemologies, thus valuing traditional knowledge and spiritual practices. The study underscores the role of spiritual practices in strengthening social bonds and cultural identities, contributing to the well-being of marginalized communities.